Analisis Usaha Tani dan Kesejahteraan Petani pada Agroekosistem Lahan Kering di Pedesaan Patanas - Sugiarto, Sugiarto (Jurnal Penelitian Pertanian Terapan, 2010)
The success of agriculture in economic development is maintaining national economic growth rate with broadening field of endeavor and to decrease poverty through income and welfare community improvement, especially farmer community in village. So that, this research gave a view of horticulture farm and income rate from various livelihoods, expending rate, and farmer household?s welfare who works in potato and cabbages farm. The research?s sites were taken from base agroekosistem dry land villages here are located in Panel Penelitian Nasional (Patanas)? site. The amount of respondent is 32 household. The result show that potato farm still suitable to do with each R/C ratio around 3.2 and cabagesb 2.8 in. Farmer?s household income was dominated with income of agriculture sector (46%-86%) beside of other sectors (14%-54%). Nevertheless farmer?s potato prosperous rate still low (NTPRT=0,9), and farmer?s cabbages are higher than one (NTPTP>1) It was showed that household?s potato still no welfares and cabbage farmer is welfares. Keywords : Farm, expenditure, income and welfare